Remote sensing of the physical qualities of fruits - Leekul, Prapan; Limpiti, Thanyawat; Tantisopharak, Thanawut; Yoiyod, Paiboon; Chivapreecha, Sorawat; Phongcharoenpanich, Chuwong; Krairiksh, Monai (My University, 2014)
Fruits are important exporting products for the countries in the tropical zone. Since the market requires the quality control, this paper discussed some techniques for classification of fruits which durian is an example.
Keywords: Free space measurement; Fruit quality control; Post-harvest inspection; Pre-harvest inspection